Ohne Titel. Im Jahr der Überfremdungsabstimmung II - Maltry, Urs (1944); SABZ / GEO seit/depuis 1912, Pf. 54, 3000 Bern 23; SABZ / GEO seit/depuis 1912, Pf. 54, 3000 Bern 23 (1974)
Reproduktion, Dispersion auf Karton (110x80 cm), Ohne Titel. Im Jahr der Überfremdungsabstimmung II, 1974;